TEACHING LITERACY FOR MENTALLY DISABLED USING REPETITION METHOD - Siti Rohmah; Sri Eka Lestari Nurjannah; Amelia Damayanti; Dwi Jiyan Sukmawati; Hanif Prasetyawan; Muhimatul Ifadah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This community service was aimed to help those disabled children in Al-Rifdah orphanage, started on April 2018, based on the previous assessement, the appropriate method is repetition. Seven children were intensively taught by using flashcard, scrambled word, and other media. The children were able to follow the instruction, able to read word and sentence. Face to face interaction and private atmosphere is a need by repetition, helped by gesture, twice in week. That was why, one tutor handled one child. However, the need for those children is not only indicated by letters recognition, or follow the instruction, but engaging communication is also a need for them. Gradually, this treatment can also help them to co communication, but of course time which is needed ismuch longer than those ordinary people. Keywords :Mentally Disabled, Alphabet, Repetition Method